The Use of Code Mixing in the Japanese Viral Song Entitled “Shinunoga E-Wa” - Kireina Fernanda Utomo; Ismatul Khasanah (Journal of Japanese Language Education and Linguistics, 2023)
Numerous languages are spoken in various countries. It is widely acknowledged that English holds the status of a worldwide language. English is frequently employed as a language of code mixing within the context of musical compositions. In the viral Japanese song titled "Shinunoga E-Wa" by Fujii Kaze, there is an amalgamation of Japanese and English linguistic elements. This study refers to the work of Lee (2004), who categorized the findings into six distinct categories of English code mixing. The present study employs a qualitative methodology known as content analysis. The data source utilized in this study originates from the song titled "Shinunoga E-Wa". The data was obtained through purposive sampling in order to select samples that possess specific criteria (Sugiyono, 2020). According to Lee (2004), the findings indicated the presence of two distinct forms of code mixing, specifically five variations related to aesthetic elements and an additional five variations associated with the expression of unresolved identity. The utilization of English code mixing demonstrates the efficacy of promoting Shinunoga E-Wa's music on social media platforms, extending its reach beyond the confines of Japan's mainstream audience.